Keabsahan Akta Notaris Pewarisan Beda Agama Ditinjau Dari Hukum Islam dan Kitab Undang-Undang Hukum Perdata - Pertiwi, A. Trisnawati Ayu; Lukman, Arsin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The family is born from the marriage bond between husband and wife and children. A person who dies of course becomes the heir of his inheritance which will be given to his family, both civil and Islamic inheritance law. However, in the practice of inheritance distribution, there are often disputes or disputes among heirs regarding the portion and portion of inheritance rights, especially in interfaith marriages whose inheritance system is carried out through a notary deed. This research is a juridical-normative research. The purpose of this study is to determine and analyze the disputes between heirs on inheritance in terms of the Civil Code and Islamic law. The results of this study are known that cases that often occur in inheritance disputes are the existence of children outside of wedlock and interfaith marriages which have implications for civil rights, especially the validity of notarial deeds in inheritance distribution. So that it is necessary to resolve inheritance disputes which can be done by means of kinship, dispute resolution, or civil claims to the Religious Courts and/or District Courts.